Research on the Power Flux-Density at the Earth’s Surface Produced by Emissions from the Fixed Beam of NGSO Constellation System - Ying HUANG; Chen JIAN; Wei LI; Kang YAN (天地一体化信息网络)
The power fl ux-density is an interference criterion for protecting terrestrial service systems from non-geostationary orbit (NGSO) constellation systems.Based on the defi nition of power fl ux density(PFD), a calculation method on the PFD produced by the emissions from the fi xed beam of NGSO constellation system was given.On the basis of describing the PFD constraint conditions of the NGSO fi xed-satellite service system given by ITU, a method for determining the limits of PFD from the NGSO constellation system was presented.Taking the Starlink system as the typical scenario, the PFD produced by telemetry, tracking, and control (TT＆amp;C) beam of the Starlink system was analyzed.The results showed that the analytical results of the given method were consistent with those of the Starlink system, and the PFD of TT＆amp;C beam in the 18.55-18.6 GHz frequency band exceeded the limit given in radio regulations.Under the current ITU framework, the number of the satellite constellation is a decisive factor for the legal use of the Ka band by NGSO constellation system.